Produção de oócitos e embriões bubalinos: efeitos da época do ano e da adição de óleo essencial de Lippia origanoides na maturação in vitro - Pereira, Emílio César Martins [UNESP] (2015)
This study aimed to develop strategies to increase the efficiency of buffalo in vitro embryo production (IVEP). In this context, we evaluated the efficiency of synchronization protocols on buffalo oocyte donor aimed at increasing the availability and quality of oocytes obtained by ovum pick-up (OPU) and the effect of the source of obtaining oocytes on the quantity and quality. In addition, we analyzed the effect of photoperiod on the quantity and quality of oocytes available on ovary, beyond the competence of those expressed by the blastocyst rate. Finally, we evaluate the effect of essential oil of Lippia origanoides (EOLO) added at concentrations of 2.5, 5.0 and 10μg/ml, on in vitro maturation (IVM) media over oocyte maturation rate, embryo quality and IVEP on cattle and buffalo. Ovaries and oocytes of animals without protocol, protocol by prior aspiration of follicles and protocol with use of steroids and gonadotropic hormones were evaluated by ultrasonography and according to the of oocyte quality. It was demonstrated not vary the follicular population, number and quality of oocytes retrieved per session between the protocols but a reduction of follicles and Grade A oocytes was noted when the follicles were aspirated previously OPU. Regarding the oocyte source (live animals and abattoir ovaries), all evaluated parameters showed superiority when oocytes were derived from abattoir ovaries. The quality of oocytes collected by OPU and IVEP buffaloes was influenced by photoperiod in the region studied, increased when daylight decreases, which was not observed in cattle. Finally, from evaluations of chromatin stained with DAPI, it was found that bovine nuclear maturation rate increased when used concentrations of 2,5μg/ml EOLO. The quality of oocytes, expressed by cell number, increased when used concentrations of 2.5 and 5μg/ml of EOLO in buffaloes. Although it has not changed the blastocyst rate of PIVE in both species, the EOLO has ...